2002
DOI: 10.1046/j.1523-1739.2002.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Factors and Stochasticity in the Evaluation of Sustainable Hunting of Tapirs

Abstract: Sustainable hunting, the extraction of game without reducing its density, is a desirable approach to the use of wildlife. Assessment of sustainable extraction in many parts of the world is difficult; it has recently been done by a method proposed by Robinson and Redford (1991): a maximum number of animals that can be extracted per unit area is calculated based on life-history parameters and density estimates. If extraction is higher than that maximum number, it is deemed unsustainable. We extended the method b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 16 publications
0
37
0
1
Order By: Relevance
“…Yet, the study was based on the use of the over simplified Robinson and Redford (1992) model, which does not take spatial factors in to account. Shape of the hunted area and the size of the surrounding population are key factors that influence the sustainability of tapir hunting (Salas and Kim 2002;Novaro et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the study was based on the use of the over simplified Robinson and Redford (1992) model, which does not take spatial factors in to account. Shape of the hunted area and the size of the surrounding population are key factors that influence the sustainability of tapir hunting (Salas and Kim 2002;Novaro et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, tapirs continue to be harvested at very high levels although they have become extremely rare in the vicinities of A'Ukre. This suggests that most of the tapirs killed in the core catchment were immigrants drawn from surrounding underharvested (or unhunted) areas as predicted by healthy patterns of landscape scale dispersal across a range of exploitation levels (Novaro et al 2000;Salas and Kim 2002). This is only possible because of the vast area of uninhabited primary forest surrounding the village catchment, which serves as a year-round source of immigrants.…”
Section: Includes Both Sympatric Congeners Rusty-margined Guan (Penementioning
confidence: 99%
“…Milner-Gulland and Akçakaya (2001) and van Vliet and Nasi (2008) showed that the major problems related to the use of simple biological indicators are paucity of available biological data even for the most common species and the difficulty of collecting data needed for a full sustainability assessment. Several authors have suggested that models for calculating sustainable harvest may produce conservative estimates (Alvard et al 1997, Robinson and Bodmer 1999, Noss 2000, Novaro et al 2000 and report levels of harvest above sustainable values, yet these levels have been maintained or increased over time with no sign of population depletion (Salas and Kim 2002). Moreover, the use of one-off sustainability indicators requires extensive fieldwork that must be repeated for each new study site if quantitative measures of game offtake or animal stocks are to be obtained (Robinson and Bodmer 1999, Sirén et al 2004, Ohl-Schacherer et al 2007, Smith 2008.…”
Section: Limits Of Approaches Classically Used To Measure the Sustainmentioning
confidence: 99%
“…Studies on sustainable hunting using spatially explicit individual-based models (Novaro et al 2000, Salas and Kim 2002, van Vliet et al 2010) have tested the role of landscape structure and dispersal characteristics that might influence the sustainability of hunting. Salas and Kim (2002) suggest that spatial factors, e.g., the shape of the hunted area and the size of the population in surrounding areas, are important in determining the harvest sustainability. Novaro et al (2000) found that dispersal has a key role in rebuilding animal populations depleted by hunting.…”
Section: Incorporating Complexity In Sustainability Assessments Of Bumentioning
confidence: 99%